2019
DOI: 10.1155/2019/7430717
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Differentiation of Polygonum multiflorum Radix and Polygoni multiflori Radix Preaparata through the Quantitative Analysis of Multicomponents by the Single-Marker Method

Abstract: The quantitative analysis of multicomponents by the single-marker (QAMS) method was established and the relationship between F value (the ratio of the sum of the contents of emodin-8-O-β-D-glucopyranoside and physcion-8-O-β-D-glucopyranoside to the sum of the contents of emodin and physcion) and the steaming time was found to identify and differentiate Polygonum multiflorum Radix and its processed product. Emodin was considered as the control substance, and the correction factors of physcion, emodin-8-O-β-D-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Tiêu chuẩn cơ sở cho sản phẩm sau chế biến được đề xuất với các chỉ tiêu gồm mô tả, định tính, độ ẩm, chất chiết được trong dược liệu và định lượng. Về chỉ tiêu định lượng, Luo và cộng sự (2019) dựa trên kết quả phân tích 66 mẫu HTOĐ thô và 106 mẫu HTOĐ chế đã đề xuất phương pháp phân biệt HTOĐ thô và HTOĐ chế là dựa vào tỷ lệ tương đối giữa các thành phần thay vì dựa trên hàm lượng tuyệt đối của từng thành phần hóa học chủ yếu là do có sự khác biệt rõ rệt về hàm lượng THSG và EM giữa các vùng địa lý khác nhau, giữa các mẫu có thời gian trồng khác nhau [10]. Từ kết quả thực nghiệm và qua tham khảo tài liệu, đề xuất chỉ tiêu định lượng HTOĐ chế phải chứa ≤ 1,36% THSG tính theo dược liệu khô kiệt, tỷ lệ EM : THSG không thấp hơn 3,57%.…”
Section: Xây Dựng Tiêu Chuẩn Cơ Sở Cho Hà Thủ ô đỏ Sau Khi Chế Biếnunclassified
“…Tiêu chuẩn cơ sở cho sản phẩm sau chế biến được đề xuất với các chỉ tiêu gồm mô tả, định tính, độ ẩm, chất chiết được trong dược liệu và định lượng. Về chỉ tiêu định lượng, Luo và cộng sự (2019) dựa trên kết quả phân tích 66 mẫu HTOĐ thô và 106 mẫu HTOĐ chế đã đề xuất phương pháp phân biệt HTOĐ thô và HTOĐ chế là dựa vào tỷ lệ tương đối giữa các thành phần thay vì dựa trên hàm lượng tuyệt đối của từng thành phần hóa học chủ yếu là do có sự khác biệt rõ rệt về hàm lượng THSG và EM giữa các vùng địa lý khác nhau, giữa các mẫu có thời gian trồng khác nhau [10]. Từ kết quả thực nghiệm và qua tham khảo tài liệu, đề xuất chỉ tiêu định lượng HTOĐ chế phải chứa ≤ 1,36% THSG tính theo dược liệu khô kiệt, tỷ lệ EM : THSG không thấp hơn 3,57%.…”
Section: Xây Dựng Tiêu Chuẩn Cơ Sở Cho Hà Thủ ô đỏ Sau Khi Chế Biếnunclassified
“…e HCA was applied to analyze the concentrations of GC, G, GV, V, GH, and H. e result indicated that 54 batches of commercial SRs (the 51st batch of SR was self-contained, not considered) were divided into two categories as shown in Figure 5. On the one hand, Cluster 1 consisted of 45 batch samples (34,55,14,54,1,11,4,15,36,39,10,40,41,42,35,18,47,7,28,43,46,23,27,50,16,29,2,3,5,21,9,12,8,38,19,44,13,37,24,48,26,20,32,33,30), in which their total content of six components was not more than 8 mg•g −1 . On the other hand, the remaining 9 batch samples (6,31,25,22,45,…”
Section: Hcamentioning
confidence: 99%
“…Meanwhile, the remaining 12 batch samples (12, 23, 5, 38, 9, 8,47,28,46,21,16,43) were attributed to Cluster 2, where the ratio was less than 10%. It was indicated that these three chromone aglycones were so important that they could be used as quality indicators for the quality evaluation of SR. Last but not least, based on the results of the twice cluster analysis, samples of the Cluster 2 (6,31,25,22,45,53,17,49,52) in the first HCA were all contained to the Cluster 1 (32,54,14,19,20,4,33,15,48,25,30,51,49,52,26,1,6,31,45,24,41,11,42,27,10,17,50,34,44,53,55,22,2,18,3,…”
Section: Hcamentioning
confidence: 99%
See 1 more Smart Citation
“…The method can achieve the synchronized measurement of multiple components by the intrinsic function and proportional relationship of the active ingredients and the introduction of RCF through the determination of only one component of the internal reference standard (IRS) [ 6 ]. It avoids the separation and purification of complex components [ 7 ] and greatly reduces the time and economic cost of quality control [ 8 , 9 ]. Moreover, this method, which improved the practicability and feasibility of quality control [ 10 ], is considered to be a better choice for quality control [ 11 – 15 ].…”
Section: Introductionmentioning
confidence: 99%